Continuity of traditions and innovation in modern landscape design in China - Ivashko, Yulia; Chang, Peng; Zueva, Polina; Ding, Yang; Kuzmenko, Tetiana (Landscape Architecture and Art, 2021)
The article analyzes the features of traditional Chinese landscape design and its impact on the landscape design of modern Chinese parks. The purpose of the article is to compare the historical gardens and modern parks of China in order to determine the continuity and at the same time the features of innovation. The main difference between historical gardens and modern parks is emphasized: historical gardens were aimed at creating a calm, serene atmosphere of contemplation of nature; modern parks often combine traditional landscape techniques and the function of entertainment. The main historical landscape techniques provided for the presence of a lake and artificial mountains as symbols of immortality, a constant change of views, contemplation of the landscape through the opening as a picture in a frame, the inclusion of a small garden in the large, partitioning the space with "green screens". Modern parks in China still inherit these techniques in general: they have reservoirs, a lot of greenery, park pavilions, but there are already views from distant points, the parks are surrounded by a wall of skyscrapers, entertaining attractions have appeared in them, and in the evenings they are illuminated with bright illumination. Despite their attractiveness and modernity, the atmosphere of the Chinese garden has changed from a secluded personal to a public character, as can be seen in the examples of modern parks in Xi’an and Hong Kong.